Cumulative cisplatin dose in concurrent chemoradiotherapy for head and neck cancer: A systematic review. (14th July 2015) - Strojan, Primož; Vermorken, Jan B.; Beitler, Jonathan J.; Saba, Nabil F.; Haigentz, Missak; Bossi, Paolo; Worden, Francis P.; Langendijk, Johannes A.; Eisbruch, Avraham; Mendenhall, William M.; Lee, Anne W. M.; Harrison, Louis B.; et al.
Abstract: Background: The optimal cumulative dose and timing of cisplatin administration in various concurrent chemoradiotherapy protocols for nonmetastatic head and neck squamous cell carcinoma (HNSCC) has not been determined. Methods: The absolute survival benefit at 5 years of concurrent chemoradiotherapy protocols versus radiotherapy alone observed in prospective randomized trials reporting on the use of cisplatin monochemotherapy for nonnasopharyngeal HNSCC was extracted. In the case of nonrandomized studies, the outcome results at 2 years were compared between groups of patients receiving different cumulative cisplatin doses. Results: Eleven randomized trials and 7 nonrandomized studies were identified. In 6 definitive radiotherapy phase III trials, a statistically significant association ( p  = .027) between cumulative cisplatin dose, independent of the schedule, and overall survival benefit was observed for higher doses. Conclusion: Results support the conclusion that the cumulative dose of cisplatin in concurrent chemoradiation protocols for HNSCC has a significant positive correlation with survival. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E2151–E2158, 2016